Strategy Planning For Tiara Bunda Elementary School Bandung - Fransiska, Fransiska; Lantu, Donald Crestofel (The Indonesian Journal of Business Administration, 2013)
Education is one of the important things to create good human resources.It is purpose to improve their potential which is to have a spiritual power, self-control, manner, intelligent, attitude nobility, and skills for themselves, community and the nation. There are some levels of education. Education level is a step which is set based on the improvement of the students, the purpose, and the improvement skills. Tiara Bunda Foundation Bandung runs an education business established on October 12, 2006. Provide from preschool to elementary. But for this paper, author focus on the elementary.The research method used is to analyse the internal and external situation in Tiara Bunda School. Questionnaire also used to find information from internal respondents (parents) and some external analysis such as the school’s competitors or the new curriculum challenges. The result of this study is to find some suitable strategies to increase costumer’s trust, as well as the teachers and the learning methods Also expected to be the solution about problems for Tiara Bunda development Key Words : Elementary school, uniqueness of learning, external and internal situations, business strategy